Synthesis and Characterization of All Renewable Resources Based Branched Polyester: Poly(2, 5-furandicarboxylic acid-co-glycerol). (21st July 2013) - Amarasekara, Ananda S.; Razzaq, Ashfaqur; Bonham, Paul
Abstract : Condensation of all renewable resources based monomers 2, 5-furandicarboxylic acid and glycerol in the presence of 2 mol% Sb2 O3 catalyst at 210°C gives a branched polyester resin in 70% yield. This resin was characterized by elemental analysis, 1 H, 13 C NMR, FT-IR, and TGA-DTG.